Criminal Legal Liability for Health Workers in Cases of Medical Malpractice - Yeni Nuraeni (Faculty of Law, Universitas Pekalongan, 2021)
Medical malpractice is an event that involves errors, negligence, or actions that do not comply with medical standards which can cause serious injury and even death to the patient. Liability for criminal acts of malpractice is presently in the spotlight due to the lack of clarity surrounding the applicable legal rules. Due to the lack of clarity in the legal standards regarding the criteria for malpractice, this is the case. The purpose of this study is to investigate aspects of criminal law pertaining to the responsibility of healthcare professionals in cases of medical malpractice. This study will compile data from relevant laws and regulations, court decisions, and the most recent literature on medical malpractice cases using normative legal research methods. A data analysis will be conducted in order to comprehend the criminal law mechanism applicable to health care professionals who commit medical malpractice. Article 360 paragraphs (1) and (2) of the Criminal Code, which contain elements of negligence (kulpa) of doctors or medical personnel, as well as the principal laws governing matters pertaining to the subject and objects in health, namely Law Number 29 of 2004 concerning Medical Practice and Law Number 44 of 2009 concerning Hospitals and Health Law, contain the legal regulations pertaining to medical malpractice. In addition, criminal liability for medical personnel who perpetrate malpractice may take the form of written warnings, revocation of licenses to practice, and re-schooling, which is the requirement to attend medical educational institutions. However, criminal responsibility can be requested for actions that result in severe injury or death due to a doctor's negligence towards a patient..